Efficient Simulation for Fixed-Receiver Bistatic SAR with Time and Frequency Synchronization Errors - Yan, Feifei; Chang, Wenge; Li, Xiangyang (Společnost pro radioelektronické inženýrství, 2015)
Time and frequency synchronization is the key technique of bistatic synthetic aperture radar (BiSAR) system, and raw data simulation is an effective tool for verifying the time and frequency synchronization techniques. According to the two-dimensional (2-D) frequency spectrum of fixed-receiver BiSAR with time and frequency synchronization errors, a rapid raw data simulation method is proposed in this paper. Through 2-D inverse Stolt transform in 2-D frequency domain and phase compensation in Range-Doppler frequency domain, this method can realize two-dimensional spatial variation simulation for fixed-receiver BiSAR with time and frequency synchronization errors in a reasonable time consumption. Then the simulation efficiency of scene raw data can be significantly improved. Simulation results of point targets and extended scene are presented to validate the feasibility and efficiency of the proposed simulation method.
Keywords: Simulation; BiSAR; fixed-receiver; inver Stolt transform; time and frequency synchronization errors